Jesus the great philosopher : rediscovering the wisdom needed for the good life - Pennington, Jonathan T. (Grand Rapids, Michigan : Brazos Press, a division of Baker Publishing Group, 2020)
"A highly regarded New Testament scholar and popular teacher helps us rediscover what the Bible says about living whole, meaningful, and flourishing lives"--
Includes bibliographical references.
Keywords: Jesus Christ -- Teachings; Wisdom